Key Technologies of Machine Vision for Precision Measuring of Profile Deviations - Dongyuan Ge; Xifan Yao; Wenjiang Xiang; Haizhi Wang; Min Liu; Xuejun Wen (Jixie chuandong, 2019)
In this paper novel measuring methods for profile deviation are proposed based on machine vision. After the tangent point of the basic circle and the normal line of the tooth profile through a sampled point are obtained， angles of vectors determining by the tangent point and the discrete points of the corresponding theoretical involute are obtained. Then the intersection point between the normal line of the tooth profile through a sampled point and the theoretical involute is obtained by using the operations of "comparison" and "XOR". Finally profile deviations are measured in the normal direction of the profile involute， which makes the tested results be consistent with its definitions. In the experiment， the obtained profile deviation is 6.944 3 μm， which demonstrates the proposed method of profile deviations test based on machine vision can meets the need of precision in engineering practice.